Synergistic effects of levo-tetrahydropalmatine and low-dose naltrexone on nicotine conditioned place preference in mice: a dual-target strategy based on dopamine and opioid systems - Feng, Kun; Zhao, Yiran; Liu, Lu; Kang, Shan; Yu, Mingming; Sy, Sherwin K. B.; Lv, Zhihua; Yan, Meixing (Frontiers in Pharmacology, 2026)
BackgroundNicotine addiction is a major public health challenge, with existing pharmacological interventions often limited by suboptimal efficacy, adverse effects and withdrawal symptoms.ObjectivesThis study explores the effects of combining levo-tetrahydropalmatine (l-THP), a dopamine receptor antagonist, with low-dose naltrexone (LDN), an opioid receptor antagonist, on nicotine-induced conditioned place preference (CPP) in mice.MethodsThe combined therapeutic effects of l-THP and LDN on nicotine was evaluated using a mouse CPP paradigm. Male Kunming mice were subjected to nicotine-induced CPP, followed by treatment with l-THP, LDN, or their combination. Behavioral assessments were conducted, and plasma β-endorphin levels were measured using enzyme linked immunosorbent assay.ResultsA 10 mg/kg l-THP alone significantly attenuated CPP, while LDN alone showed no significant effect. The combination of 10 mg/kg l-THP and 0.3 mg/kg LDN produced a synergistic reduction in nicotine-seeking behavior, effectively reversing the CPP effect. The combination therapy was associated with an increased plasma β-endorphin levels, suggesting a modulation of the endogenous opioid system.ConclusionThese findings indicate that the combination therapy based on dual-action mechanism of l-THP and LDN, targeting both dopamine and opioid pathways, effectively attenuates nicotine-induced CPP in mice, which may offer a potential treatment for nicotine addiction. The combination enhances therapeutic efficacy within the nicotine-induced CPP paradigm and correlates with an elevation of β-endorphin levels.